Cenotes (sinkholes) of the Yucatan Peninsula, Mexico, as a habitat of adult trematodes of fish - Scholz, T; Vargas-Vázquez, J; Moravec, F; Vivas-Rodríguez, C; Mendoza-Franco, E (Folia parasitologica, 1995)
Examination of a total of 581 fish specimens of 15 species from 39 cenotes (sinkholes) in the Yucatan Peninsula, southeastern Mexico, revealed the presence of 10 species of adult trematodes. These were as follows: Saccocoelioides sogandaresi Lumsden, 1963, Saccocoelioides sp. (family Haploporidae), Cichlasotrema ujati Pineda et Andrade, 1989 (Angiodictyidae), Crassicutis cichlasomae Manter, 1936 (Homalometridae), Magnivitellinum simplex Kloss, 1966 (Macroderoididae), Stunkardiella minima (Stunkard, 1938) (Acanthostomidae), Oligogonotylus manteri Watson, 1976 (Cryptogonimidae), Genarchella tropica (Manter, 1936), G. astyanactis (Watson, 1976), and G. isabellae (Lamothe-Argumedo, 1977) (Derogenidae). Saccocoelioides sogandaresi is reported from Mexico for the first time. Poecilia velifera and P. latipunctata for S. sogandaresi, Cichlasoma octofasciatum for C. cichlasomae, Cichlasoma friedrichstahli and C. meeki for O. manteri, and C. meeki, C. octofasciatum and Gobiomorus dormitor for G. isabellae represent new host records. Most species found are described and figured and their host range and distribution are discussed.
Keywords: ryby; Fishes; infekce červy třídy Trematoda; Trematode Infections; Animals; sladká voda; Mexico; Fresh Water; Mexiko; zvířata; Trematoda